Lifecourse Activity Participation From Early, Mid, and Later Adulthood as Determinants of Cognitive Aging: The Lothian Birth Cohort 1921 - Gow, Alan J. (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: To examine potential sensitive periods for activity participation across adulthood to reduce cognitive decline and to determine whether associations persist after accounting for the lifetime stability of cognitive ability. METHOD: The Lothian Birth Cohort 1921 is a longitudinal study of cognitive aging. Participants were born in 1921 and most completed a mental ability test at the age of 11 years. Cognitive assessments were completed at mean ages 79 (N = 550), 83 (N = 321), 87 (N = 235), and 90 years (N = 129). Participants provided retrospective details of their activity participation for young (20–35 years), mid (40–55 years), and later adulthood (60–75 years), and contemporaneously at age 79. RESULTS: Associations between activity and the level of, and change in, cognitive ability in old age were examined with latent growth curve models. Accounting for demographics and childhood cognitive ability, engagement in leisure activities in midlife was positively associated with cognitive ability level (path coefficient = .32), whereas higher physical activity in later adulthood was associated with less cognitive decline (.27). DISCUSSION: The findings support a lifecourse approach in identifying determinants of cognitive aging; leisure and physical activity during different periods of adulthood may enhance cognitive abilities or reduce decline.